The Dynamic Impact of Macroeconomic Uncertainty on Corporate Accounting Policy Choices - Zhang, Xueyue; Jiang, Xiaoyun (Transactions on Economics, Business and Management Research, 2026)
Against the backdrop of an increasingly complex macroeconomic environment, macroeconomic uncertainty has become an important external factor shaping corporate decision-making. Using a sample of Chinese A-share listed firms, this paper examines the impact of macroeconomic uncertainty on corporate accounting policy choices and their dynamic features. The results show that macroeconomic uncertainty significantly affects corporate accounting policy choices and, on average, strengthens firms’ strategic financial reporting behavior. Further analysis indicates that this effect is not limited to the current period, but persists in the short run and gradually weakens over time. In addition, the effect of macroeconomic uncertainty on corporate accounting policy choices is more pronounced among firms facing stronger financing constraints. This study extends the literature on the determinants of corporate accounting policy choices from the perspective of changes in the macroeconomic environment, and highlights the intertemporal response of firms’ financial reporting behavior to external uncertainty shocks. The findings provide new empirical evidence for understanding corporate financial reporting decisions under macroeconomic uncertainty and offer useful implications for regulators, investors, and corporate managers.